2021
DOI: 10.1002/jmv.27270
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination versus infection with SARS‐CoV‐2: Establishment of a high avidity IgG response versus incomplete avidity maturation

Abstract: Avidity is defined as the binding strength of immunoglobulin G (IgG) toward its target epitope. Avidity is directly related to affinity, as both processes are determined by the best fit of IgG to epitopes. We confirm and extend data on incomplete avidity maturation of IgG toward severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) nucleoprotein (NP), spike protein‐1 (S1), and its receptor‐binding domain (RBD) in coronavirus disease 2019 (COVID‐19) patients. In SARS‐CoV‐2‐infected individuals, an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 49 publications
10
60
0
1
Order By: Relevance
“…After the first vaccination nearly all vaccinees exhibited only low to intermediate avid anti-SARS-CoV-2 IgG, while after the second vaccine dose IgG of high avidity appeared in all cases. These results confirm and expand the existing knowledge on the development of highly avid anti-SARS-CoV-2 IgG after a second vaccination with an mRNA vaccine [28]. In line with this, VNA > 1:10 against the previously prevalent SARS-CoV-2 VOC B.1.1.7 (alpha) were observed after second immunisation which confirms our recent study [22].…”
Section: Discussionsupporting
confidence: 92%
“…After the first vaccination nearly all vaccinees exhibited only low to intermediate avid anti-SARS-CoV-2 IgG, while after the second vaccine dose IgG of high avidity appeared in all cases. These results confirm and expand the existing knowledge on the development of highly avid anti-SARS-CoV-2 IgG after a second vaccination with an mRNA vaccine [28]. In line with this, VNA > 1:10 against the previously prevalent SARS-CoV-2 VOC B.1.1.7 (alpha) were observed after second immunisation which confirms our recent study [22].…”
Section: Discussionsupporting
confidence: 92%
“…In COVID-19 patients, affinity maturation is potentially impaired by the dysfunction of germinal centres associated with severe disease [40] , [41] . Actually, longitudinal studies on functional affinity maturation after natural infection have produced heterogeneous results [21] , [30] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] with gender, age and COVID-19 severity likely playing a role in driving divergent pathways [42] , [43] , [48] . On the contrary, in vaccine recipients, affinity maturation seems to be guaranteed by the uploading and persistence of viral Spike antigen on dendritic cells of germinal centers up to 12 weeks after liposomal mRNA inoculation [54] , which in turn provide a solid background for long-term antigen presentation in germinal centres [55] and eventual achievement of high avidity values [30] , [35] , [36] , [56] .…”
Section: Discussionmentioning
confidence: 99%
“…Actually, longitudinal studies on functional affinity maturation after natural infection have produced heterogeneous results [21] , [30] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] with gender, age and COVID-19 severity likely playing a role in driving divergent pathways [42] , [43] , [48] . On the contrary, in vaccine recipients, affinity maturation seems to be guaranteed by the uploading and persistence of viral Spike antigen on dendritic cells of germinal centers up to 12 weeks after liposomal mRNA inoculation [54] , which in turn provide a solid background for long-term antigen presentation in germinal centres [55] and eventual achievement of high avidity values [30] , [35] , [36] , [56] . Notably, a study from Struck et al [30] , which directly assessed avidity of anti-SARS-CoV-2 sera from vaccinated subject using the chaotropic agent urea, have provided strong evidence that avidity significantly increases in the first two months after vaccination, which may also explains the persistence of high neutralizing bioactivity in the face of declining anti-RBD IgG over a longer period of time, as this study showed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] Although there was an initial but limited increase in the avidity of IgG directed toward SARS-CoV-2 nucleoprotein (NP), spike protein-1 (S1) and the receptor-binding domain of the spike protein (RBD) after SARS-CoV-2 infection, avidity persisted at an untypical low or intermediate level, even up to 1 year after primary infection. 15 This novel picture of incomplete avidity maturation raised problems for the differentiation between the stages of infection. Even more importantly, these findings seemed to indicate that infections with SARS-CoV-2 might not necessarily lead to protective immunity.…”
mentioning
confidence: 99%